Advanced functional textiles and polymers - Ul-Islam, Shahid; Butola, B. S. (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2020)
"This book on advanced functional textiles and polymers will offer a comprehensive view of cutting-edge research in newly discovered areas such as flame retardant textiles, antimicrobial textiles, insect repellent textiles, aroma textiles, medical-textiles, smart textiles, and nano-textiles etc. The second part the book provides innovative fabrication strategies, unique methodologies and overview of latest novel agents employed in the research and development of functional polymers"--